Association Between Age and Fibrinolytic Success in ST-Segment Elevation Myocardial Infarction Patients Treated with Streptokinase: Iswandi Darwis, Yahya Kemas Abdillah, Icmi Dian Rochmawati - iswandi darwis (Jurnal Kedokteran Universitas Lampung, 2026)
Background: ST-Segment Elevation Myocardial Infarction (STEMI) is a cardiovascular emergency requiring immediate reperfusion therapy. Fibrinolytic therapy remains an important treatment option, particularly in healthcare facilities where access to primary Percutaneous Coronary Intervention (PCI) is limited. Advanced age has been associated with poorer prognosis in STEMI patients; however, the relationship between age and fibrinolytic success remains controversial. Objective: To analyze the association between age and fibrinolytic success among STEMI patients treated with streptokinase. Methods: This retrospective cross-sectional analytic study utilized medical record data from STEMI patients who received fibrinolytic therapy at Yukum Medical Centre Hospital between January 2024 and December 2025. Subjects were selected using a total sampling method. Patients were categorized into two age groups: <60 years and ≥60 years. Successful fibrinolysis was defined as a ≥50% resolution of ST-segment elevation within 60–90 minutes after fibrinolytic administration. The association between age and fibrinolytic success was analyzed using the Chi-square test, with a significance level of p<0.05. Results: A total of 98 patients met the inclusion criteria, with a mean age of 56.24 ± 11.68 years. Most participants were male (73.47%). Successful fibrinolysis was observed in 49 patients (50.0%). In the ≥60 years age group, successful fibrinolysis occurred in 16 patients (44.44%), whereas 33 patients (53.23%) in the <60 years group achieved successful fibrinolysis. Statistical analysis demonstrated no significant association between age and fibrinolytic success (PR=1.188; 95% CI: 0.800–1.763; p=0.402). Conclusion: There was no significant association between age and fibrinolytic success among STEMI patients treated with streptokinase. Reperfusion success is likely influenced more by other factors, including treatment delay, clinical characteristics, and coronary thrombotic burden. Keywords: ST-segment elevation myocardial infarction, STEMI, fibrinolysis, streptokinase, age.